2011
DOI: 10.1002/wmts.1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of P2X receptors

Abstract: P2X receptors are ligand-gated cation channels that mediate many of the extracellular actions of adenosine 5 -triphosphate (ATP). The genes encoding seven different P2X subunits, P2X1-7, have been cloned and when expressed alone all P2X subunits form functional receptors, except P2X6, which usually only assembles in a heteromeric form. Subunits can also interact with each other and to date seven functional heteromultimers with pharmacological and/or biophysical properties that differ from the individual homomu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 80 publications
1
30
0
Order By: Relevance
“…In contrast, a maximally effective concentration of AR-C69931MX (1 M) had no significant effect on contractions elicited by KCl (40 mM) (94.5 Ϯ 3.7% of control; n ϭ 6) or UDP (300 M) (95.7 Ϯ 1.5% of control; n ϭ 3). Our previous data indicated that P2X1 receptors mediate more than half of the response to ATP (Chootip et al, 2002(Chootip et al, , 2005, and, consistent with this, the contractions elicited by ATP (300 M) were virtually abolished by the combined blockade of P2X1 and P2Y 12 receptors with the P2X1 antagonist NF449 (30 M) (Syed et al, 2010;Syed and Kennedy, 2012) and AR-C69931MX (1 M) (Fig. 2, c and d).…”
Section: Atp-sensitivesupporting
confidence: 83%
“…In contrast, a maximally effective concentration of AR-C69931MX (1 M) had no significant effect on contractions elicited by KCl (40 mM) (94.5 Ϯ 3.7% of control; n ϭ 6) or UDP (300 M) (95.7 Ϯ 1.5% of control; n ϭ 3). Our previous data indicated that P2X1 receptors mediate more than half of the response to ATP (Chootip et al, 2002(Chootip et al, , 2005, and, consistent with this, the contractions elicited by ATP (300 M) were virtually abolished by the combined blockade of P2X1 and P2Y 12 receptors with the P2X1 antagonist NF449 (30 M) (Syed et al, 2010;Syed and Kennedy, 2012) and AR-C69931MX (1 M) (Fig. 2, c and d).…”
Section: Atp-sensitivesupporting
confidence: 83%
“…For example, 3′-benzylamino-3′-deoxy-ATP was found to be very potent in the guinea-pig bladder, but was inactive at P2Y receptors. There are reviews that discuss the developments of P2X receptor antagonists [240,260,651].…”
Section: P2x Receptors Mediating Contraction Of the Bladdermentioning
confidence: 99%
“…Many P2XR antagonists have been identified [5355], including a subtype non-selective, competitive antagonist called suramin. A mutational study [56] identified K138 in the human P2X1 receptor (corresponding to D141 in zP2X4R) as a possible suramin-interacting residue.…”
Section: P2x Receptorsmentioning
confidence: 99%
“…This lends support to the suggestion that competitive antagonists may occupy the wider inter-protomer ridge above the FCC (similar to ATP in the distal orientation), thereby maintaining the closure of the pre-M2 loop. Many other P2XR antagonists are described as noncompetitive, and their binding sites remain unknown [5355]. …”
Section: P2x Receptorsmentioning
confidence: 99%